2021
DOI: 10.3390/su132111832
|View full text |Cite
|
Sign up to set email alerts
|

Peer-to-Peer Confirmation, Positive Automatic Thoughts, and Flourishing of Computer Programming E-Learners

Abstract: Computer programming e-learners faced stressful life circumstances and educational changes that affected the world during the COVID-19 pandemic. As the cognitive model of flourishing focuses on cognitions rather than situations themselves, it was deemed significant to identify peer-to-peer confirmation, positive automatic thoughts, flourishing, and the links between these study variables in a group of computer programming e-learners and compare the results with other e-learners. This study applied the Flourish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 117 publications
2
1
0
Order By: Relevance
“…The findings of this study also demonstrated that positive automatic thoughts are positively associated with flourishing, which is also in line with previous research (Howell 2009; Howell and Buro 2014; Dirzyte et al 2021). Most importantly, this study showed that positive automatic thoughts mediate links between negative cognitions and flourishing, which means that efforts to improve students' positive cognitions may contribute to their flourishing.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study also demonstrated that positive automatic thoughts are positively associated with flourishing, which is also in line with previous research (Howell 2009; Howell and Buro 2014; Dirzyte et al 2021). Most importantly, this study showed that positive automatic thoughts mediate links between negative cognitions and flourishing, which means that efforts to improve students' positive cognitions may contribute to their flourishing.…”
Section: Discussionsupporting
confidence: 92%
“…However, the effect of personal maladjustment was insignificant. The findings that positive automatic thoughts positively predict flourishing were found in other studies (Dirzyte et al 2021), as well as the results linking negative self-concept to poor mental wellbeing.…”
Section: Discussionsupporting
confidence: 79%
“…One approach we commonly employ in our classrooms to support self-efficacy is collaborative learning. Numerous studies in a variety of disciplines have shown that collaborative, peer-to-peer interactions can enhance self-efficacy (Samiullah, 1995;Fencl and Scheel, 2005;Sidelinger and Booth-Butterfield, 2010;Sollitto et al, 2013;Lewis et al, 2021;Stoeckel and Roehrig, 2021), especially in the context of learning to code (McDowell et al, 2003;Hanks et al, 2011;Salleh et al, 2011;Dirzyte et al, 2021). While peer-to-peer learning can be challenging to accomplish virtually, the use of breakout rooms can be one way to facilitate these types of interactions.…”
Section: Functioning Computersmentioning
confidence: 99%